First-Line Palliative Chemotherapy for Esophageal and Gastric Cancer: Practice Patterns and Outcomes in the General Population. Issue 10 (October 2021) - Merchant, Shaila J.; Kong, Weidong; Gyawali, Bishal; Hanna, Timothy P.; Chung, Wiley; Nanji, Sulaiman; Patel, Sunil V.; Booth, Christopher M.
Abstract : PURPOSE: Clinical trials have shown that palliative chemotherapy (PC) improves survival in patients with incurable esophageal and gastric cancer; however, outcomes achieved in routine practice are unknown. We describe treatment patterns and outcomes among patients treated in the general population of Ontario, Canada. METHODS: The Ontario Cancer Registry was used to identify patients with esophageal or gastric cancer from 2007 to 2016, and data were linked to other health administrative databases. Patients who received curative-intent surgery or radiotherapy were excluded. Factors associated with the receipt of PC were determined using logistic regression. First-line PC regimens were categorized, and trends over time were reported. Survival was determined using the Kaplan-Meier method. RESULTS: The cohort included 9, 848 patients; 22% (2, 207 of 9, 848) received PC. Patients receiving PC were younger (mean age, 63 v 74 years; P < .0001) and more likely male (71% v 65%; P < .0001). Thirty-seven percent of non-PC patients saw a medical oncologist in consultation. Over the study period, utilization of PC increased (from 11% in 2007 to 19% in 2016; P < .0001), whereas the proportion of patients receiving triplet regimens decreased (65% in 2007 to 56% in 2016; P = .04). In the PC group, the median overall and cancer-specific survival from treatment initiation was 7.2 months. CONCLUSION: One fifth of patients with incurable esophageal and gastric cancer in the general population receive PC. Median survival of patients treated in routine practice is inferior to that in clinical trials. Only one third of patients not treated with PC had consultation with a medical oncologist. Further work is necessary to understand low utilization of PC and medical oncology consultation in this patient population.